A model for improving cold supply chain performance: an integrated FISM/BWM/ANP approach. (18th April 2022) - Jafarpour, Masoomeh; Shojaei, Payam; Alimohammadlou, Moslem
The importance of preserving perishable products, especially those with a short shelf-life, has led to the formation of a new sub-branch in the supply chain literature called the cold supply chain (CSC). This study sought to develop a model for improving the performance of the CSC in the dairy industry. First, the study identified the factors affecting the improvement of CSC performance by reviewing the literature and interviewing experts. The relationships between the factors were then explored and the level of each factor was found through fuzzy interpretive structural modelling (FISM). Finally, the priorities of all factors were identified via an integrated version of best-worst method (BWM) and analytic network process (ANP). The results showed that 'warehousing and quality of storage' and 'relationship with customer' had the highest priorities in improving the CSC performance. The results of this study could help managers dealing with dairy businesses to improve their CSC performance.